2022
DOI: 10.1073/pnas.2201240119
|View full text |Cite|
|
Sign up to set email alerts
|

Cooperative redox and spin activity from three redox congeners of sulfur-bridged iron nitrosyl and nickel dithiolene complexes

Abstract: The synthesis of sulfur-bridged Fe–Ni heterobimetallics was inspired by Nature’s strategies to “trick” abundant first row transition metals into enabling 2-electron processes: redox-active ligands (including pendant iron–sulfur clusters) and proximal metals. Our design to have redox-active ligands on each metal, NO on iron and dithiolene on nickel, resulted in the observation of unexpectedly intricate physical properties. The metallodithiolate, (NO)Fe(N 2 S 2 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…13 Consistently, the two reductions of the [FeMFe] 2+ series are {Fe(NO)} 7/8 based, with the first process leading to a mixed valence {Fe(NO)} 7 –M II –{Fe(NO)} 8 unit, and the second event producing the fully reduced {Fe(NO)} 8 –M II –{Fe(NO)} 8 complex. In prior studies, we observed the rare {Fe(NO)} 8 unit in the case of doubly reduced [Fe–Ni] + , 10,11 but attempts to isolate the one- and two-electron reduction products of the [FeMFe] 2+ complexes have thus far been unsuccessful.…”
Section: Resultsmentioning
confidence: 96%
“…13 Consistently, the two reductions of the [FeMFe] 2+ series are {Fe(NO)} 7/8 based, with the first process leading to a mixed valence {Fe(NO)} 7 –M II –{Fe(NO)} 8 unit, and the second event producing the fully reduced {Fe(NO)} 8 –M II –{Fe(NO)} 8 complex. In prior studies, we observed the rare {Fe(NO)} 8 unit in the case of doubly reduced [Fe–Ni] + , 10,11 but attempts to isolate the one- and two-electron reduction products of the [FeMFe] 2+ complexes have thus far been unsuccessful.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, the sulfur-bridged Fe–Ni bimetallics of this study with NO on iron and dithiolene on nickel were found to produce heterobimetallics with unusual and unexpectedly intricate physical properties . Good reversibility in two redox events of the as isolated neutral bimetallic complex FeNi at −0.24 and −1.18 V led to isolation of oxidized and reduced congeners, respectively; see Figure .…”
Section: Cooperative Redox and Spin Activity In Sulfur-bridged Iron N...mentioning
confidence: 68%
“…Magnetic data (SQUID) on the dimer dication, spin topology shown in Figure 7A, found a singlet ground state with a thermally accessible triplet state that is responsible for the magnetism at 300 K (χ M T = 0.61 emu K ) explains this unexpected ferromagnetic low-energy triplet state arising from antiferromagnetic coupling of a four-radical molecular conglomerate. 2 The R 1 and R 2 distances were adjusted and benchmarked to match the DFT computed energies (Figure 7B). With both energy profiles the PHI program was used to fit J 1 and J 2 , the dominant exchange pathways.…”
Section: Cooperative Redox and Spin Activity In Sulfur-bridged Iron N...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrosylated (N 2 S 2 )­Fe­(NO) and Co­(NO) derivatives offer the possibility of exploiting the aggregative ability of sulfur to generate polymetallic products containing the redox, vibrational, and magnetic activity of the NO ligand. , In view of the numerous hydrocarbon connectors possible within the N 2 S 2 scaffold, an almost unlimited design space is conceivable. An application of these strategies toward derivatives of molybdenum, expected to be analogous to a class of [(bis-diphosphine) 2 M­(NO)­X] n + molecules, led to an unusual, asymmetric version of the basket structure of Figure .…”
Section: Introductionmentioning
confidence: 99%